Intelligent Systems in Cybernetics and Automation Control Theory - Silhavy, Radek; Silhavy, Petr.; Prokopova, Zdenka; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents real-world problems and pioneering research that reflect novel approaches to cybernetics, algorithms and software engineering in the context of intelligent systems. It gathers the peer-reviewed proceedings of the 2nd Computational Methods in Systems and Software 2018 (CoMeSySo 2018), a conference that broke down traditional barriers by being held online. The goal of the event was to provide an international forum for discussing the latest high-quality research results. .
Efficient Framework to Secure Communication in IoT using Novel Finite Field Encryption -- A Novel Template based Data Structurization Scheme for Normalizing and Analyzing Medical data -- A Novel Design and Implementation of Imaging Chip using AXI Protocol for MPSOC on FPGA -- Simple Modeling of Mobile Foreground Detection using Probabilistic Linear Estimation Approach -- An Agent-Architecture for Automated Decision Making on the Semantic Web -- An Efficient Hardware Realization of DCT Based Color Image Mosaicing System on FPGA -- A Recovery Technique for the Fog-computing-based Information and Control systems -- An Examination of Message Ferry Movement for Delay Tolerant Networks -- Comparison of ERP Systems with Blockchain Platform -- Data extraction from the distorted DCF77 signal captured using low-cost receivers -- Efficiency Comparison of Modern Computer Languages: Sorting Benchmark -- Input Output data converter for the Math engine in an Expert System -- Adaptive Software System for Optimization of the Admission and Management Process for Doctoral Students.
Keywords: Computational intelligence; Control engineering; Artificial intelligence; Computational Intelligence; Control and Systems Theory; Artificial Intelligence